A digital fibromyxoid tumor: a case report (Journal of Pathology of Nepal, 2022)
A digital fibromyxoma is a rare soft tissue tumor, which occurs in the finger and toes around the subungual and periungual region. Histopathologically, it consists of a well-circumscribed unencapsulated dermal tumor composed of spindle and stellate cells in a loose fascicular pattern embedded in a myxocollagenous stroma. We report this rare case of superficial acral fibromyxoma presenting as an asymptomatic subungual mass in the greater toe in a middle age female.